A Fiqh-Based Solution to Worship Practices During the Covid-19 Pandemic and Natural Disasters - Aminullah; Gassing, A. Qadir; Syarif, Muhammad Fazlurrahman (MUI Sulawesi Selatan, 2025)
This study aims to explore the fiqh-based solutions for the implementation of Islamic worship during the Covid-19 pandemic and natural disasters. It examines how Islamic jurisprudence provides flexibility and prioritizes public safety without compromising religious obligations in emergency contexts. Using a qualitative normative approach, this research analyzes primary sources of Islamic law, including the Qur’an, Hadith, and classical fiqh literature, supplemented by contemporary fatwas and scholarly opinions. The study also applies maqāṣid al-sharī‘ah (objectives of Islamic law) principles to interpret worship practices amid health crises and natural disasters. Findings indicate that contemporary ulama universally emphasize the obligation to preserve life (ḥifẓ al-nafs) while maintaining religious duties. Fiqh accommodates emergency circumstances by permitting modifications or delays in worship, such as congregational prayers and fasting, without nullifying their spiritual value. The research highlights consensus on using protective health measures and endorsing vaccination during fasting, emphasizing that safeguarding health takes precedence. This research contributes to the growing body of Islamic jurisprudential discourse by offering a comprehensive fiqh framework tailored to unprecedented global health emergencies and environmental catastrophes. It bridges classical legal principles with modern public health concerns, providing practical religious guidance in times of crisis. The study serves as a reference for policymakers, religious authorities, and Muslim communities to develop informed, flexible worship protocols during emergencies. It also encourages further research into fiqh responses to socio-religious challenges beyond health crises, such as in economic and family law during pandemics or disasters.